2020
DOI: 10.3390/cells9030564
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes are the Driving Force in Preparing the Soil for the Metastatic Seeds: Lessons from the Prostate Cancer

Abstract: Exosomes are nano-membrane vesicles that various cell types secrete during physiological and pathophysiological conditions. By shuttling bioactive molecules such as nucleic acids, proteins, and lipids to target cells, exosomes serve as key regulators for multiple cellular processes, including cancer metastasis. Recently, microvesicles have emerged as a challenge in the treatment of prostate cancer (PCa), encountered either when the number of vesicles increases or when the vesicles move into circulation, potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 229 publications
(265 reference statements)
0
53
0
Order By: Relevance
“…The importance of cellular crosstalk between PCa cells and to their tumor microenvironment (TME) to promote progression and metastasis has been documented in cancer research. Although a number of studies suggested the role of soluble factors in modulating TME, the potential role of exosomes in altering TME to induce tumor aggressiveness is gaining momentum [30,31]. Understanding the underlying mechanisms and cargo contents of exosomes-mediated transfer to and from PCa cells and TME at advanced stages of the disease will constitute a strong foundation on which novel and more specific therapeutic targets may be evolved.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of cellular crosstalk between PCa cells and to their tumor microenvironment (TME) to promote progression and metastasis has been documented in cancer research. Although a number of studies suggested the role of soluble factors in modulating TME, the potential role of exosomes in altering TME to induce tumor aggressiveness is gaining momentum [30,31]. Understanding the underlying mechanisms and cargo contents of exosomes-mediated transfer to and from PCa cells and TME at advanced stages of the disease will constitute a strong foundation on which novel and more specific therapeutic targets may be evolved.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are small extracellular vesicles (EVs) initially generated as intraluminal vesicles (ILVs) in endosomal multivesicular endosomes (MVEs) (Colombo et al, 2014;Möbius et al, 2002;White et al, 2006). They are released by all cell types and mediate cell-cell communication events in development, immunity, reproduction and many other physiological and disease processes, such as neurodegenerative diseases (Thompson et al, 2016) and cancer (Saber et al, 2020). In cancer, exosome cargos can modify the behaviour of recipient cells, leading to tumour progression by driving tumour cell growth and invasiveness, reprogramming the tumour microenvironment, promoting endothelial network assembly, modulating the immune response and inducing pre-metastatic niche formation (Becker et al, 2016;Comito et al, 2020;Saber et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They are released by all cell types and mediate cell-cell communication events in development, immunity, reproduction and many other physiological and disease processes, such as neurodegenerative diseases (Thompson et al, 2016) and cancer (Saber et al, 2020). In cancer, exosome cargos can modify the behaviour of recipient cells, leading to tumour progression by driving tumour cell growth and invasiveness, reprogramming the tumour microenvironment, promoting endothelial network assembly, modulating the immune response and inducing pre-metastatic niche formation (Becker et al, 2016;Comito et al, 2020;Saber et al, 2020). Exosomes are highly heterogeneous, but the mechanisms underlying this heterogeneity and the routes by which exosome signalling can be modulated have until recently, remained largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…PEVs are highly interesting group of EVs because of their percentage participation in bloodstream, as well as their increased number in patients with cancer, such as glioblastoma, gastric, lung and skin cancer, and other diseases. This makes them potentially useful as a diagnostic marker [ 79 ]. It is known that PLTs facilitate cancer metastasis.…”
Section: Pevs In Cancer Progressionmentioning
confidence: 99%
“…Therefore, angiogenesis is a critical factor in the progression of cancer. The tumor microenvironment (TME) consists of diverse cellular populations, including tumor cells, endothelial cells, fibroblasts, infiltrating immune cells (monocytes, macrophages, neutrophils, mast cells, T cells), extracellular matrix, and newly formed blood vessels [ 79 ]. The PEVs interaction with TME components could reveal their functions in cancer progression.…”
Section: Pevs In Cancer Progressionmentioning
confidence: 99%